Production Scheduling System Based on Customer Orders at AsMedia Percetakan Nganjuk (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to identify the most effective production scheduling system at AsMedia Percetakan Nganjuk to reduce delays in order fulfillment. The proposed scheduling method is based on a priority rule system with the following criteria: First Come First Served (FCFS), Short Processing Time (SPT), Long Processing Time (LPT), and Earliest Due Date (EDD). Based on the results of data analysis and discussion, the First Come First Served (FCFS) and Earliest Due Date (EDD) methods are considered superior compared to the other methods. This is based on findings that show the effectiveness of the First Come First Served (FCFS) and Earliest Due Date (EDD) methods aligns with current criteria, including minimum average completion time, maximum utilization, minimum average number of jobs in the system, and minimum delays. Therefore, the researcher recommends that AsMedia Percetakan Nganjuk use the First Come First Served (FCFS) and Earliest Due Date (EDD) methods as alternative production scheduling methods. Given the relatively high average job delays with each method used, the company is deemed less effective in production scheduling. This is evident from the relatively high average job delays with each method used. Therefore, the solution the researcher can offer to AsMedia Percetakan Nganjuk is to increase the workforce and production machine capacity.